Enhancing Performance through Work Environment, Rewards, and Employee Engagement - Mohammad Alvin Sufianto Ghozali; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative study investigates the impact of work environment and rewards on employee engagement and performance in BUMDes across Porong District. Using a sample of 104 participants, the research finds that while direct effects of work environment on employee engagement were not significant, both factors indirectly influence performance through enhanced engagement. Key findings highlight the importance of facilities and boredom alleviation in the work environment, as well as learning opportunities within rewards, in shaping performance outcomes. The study underscores the pivotal role of employee engagement, characterized by enthusiasm and support, as a mediator between these variables. The implications suggest that improving work conditions and optimizing reward systems can effectively bolster employee engagement and thereby enhance organizational performance in community-owned enterprises. Highlights: Quantitative study on work environment, rewards, and performance in BUMDes. Finds indirect impact of work environment on performance through engagement. Suggests improving conditions and rewards to boost employee engagement and performance. Keywords: Employee Engagement, Work Environment, Rewards, Performance, BUMDes